Associations between dysbiosis gut microbiota and changes of neurotransmitters and short-chain fatty acids in valproic acid model rats - Zhong, Jiu-Gen; Lan, Wan-Ting; Feng, Yan-Qing; Li, Yin-Hua; Shen, Ying-Ying; Gong, Jia-Heng; Zou, Zhi; Hou, Xiaohui (Frontiers in Physiology, 2023)
Introduction: The microbiota–gut–brain axis plays an important role in the pathophysiology of autism spectrum disorder, but its specific mechanisms remain unclear. This study aimed to explore the associations of changes in neurotransmitters and short-chain fatty acids with alterations in gut microbiota in valproic acid model rats. Methods: The autism model rats were established by prenatal exposure to valproic acid (VPA). The Morris water maze test, open field test, and three-chamber test were conducted to assess the behaviors of rats. 16S rRNA gene sequences extracted from fecal samples were used to assess the gut microbial composition. Gas and liquid chromatography–mass spectroscopy was used to identify short-chain fatty acids in fecal samples and neurotransmitters in the prefrontal cortex (PFC). Results: The results showed that 28 bacterial taxa between valproic acid model rats and control rats were identified, and the most differential bacterial taxa in valproic acid model rats and control rats belonged to metagenomic species and Lactobacillus intestinalis. Acetic acid, butyric acid, valeric acid, isobutyric acid, and isovaleric acid were significantly decreased in the valproic acid model rats compared to those in control rats. Five neurotransmitters (threonine, kynurenine, tryptophan, 5-hydroxyindoleacetic acid, denoted as 5-HIAA, and betaine aldehyde chloride, denoted as BAC) were significantly decreased, whereas betaine was increased in the prefrontal cortex of valproic acid model rats compared to control rats. A variety of neurotransmitters (≥4) were correlated with Pseudomonas, Collisella, and Streptococcus at the genus level, and they were also related to the decrease of short-chain fatty acids. Discussion: According to this study, we can preliminarily infer that gut microbiota or their metabolic productions (such as SCFAs) may influence central neurotransmitter metabolism through related pathways of the gut-brain axis. These results provide microbial and short-chain fatty acid (SCFA) frameworks for understanding the role of the microbiota–gut–brain axis in autism spectrum disorder and shed new light on autism spectrum disorder treatment.